Civil Responsibility Arising From The Expert's Work – A Comparative Study (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The difficulty faced by the judiciary in order to achieve the objective of establishing a case for the passing of this case does not hide from circumstances that do not meet the legal limit, but rather to the extent that these problems are of a technical or professional nature that exceeds the legal jurisdiction of the courts or judges. Achieving the desired justice, especially if the disputes are similar in ambiguity and overshadowed by the technical nature, which makes it difficult for the judge to understand that he is beyond the scope of his legal competence and experience in the field of law, especially with the great development of products and accompanying technical development can not be understood and understood only by the competent procession for my work Evolution. But often the law refers to the need to estimate some legal status by a competent person, as in the case of hidden defects and estimate the amount of compensation. Moreover, the judge and whatever he knows in some technical matters, but he can not know all kinds of science and knowledge, and the judge can not judge his personal knowledge. Therefore, the law permits the use of persons with sufficient knowledge in the technical field of the case pending by the judiciary through the expertise provided by the expert to the court, which facilitates the work of the judiciary and helps to prove the facts and form sufficient conviction for the issuance of the most appropriate and the most effective judgment.